2003
DOI: 10.1097/01.ta.0000070166.29649.f3
|View full text |Cite
|
Sign up to set email alerts
|

Both Primary and Secondary Abdominal Compartment Syndrome can be Predicted Early and are Harbingers of Multiple Organ Failure

Abstract: Primary and secondary ACS have similar demographics, injury severity, time to decompression from hospital admit, and bad outcome. 2 degrees ACS is an earlier ICU event preceded by more crystalloid administration. With appropriate monitoring both could be accurately predicted upon ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
238
3
32

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 340 publications
(275 citation statements)
references
References 32 publications
2
238
3
32
Order By: Relevance
“…It often results from a mismatch between the fluids required and the fluids administered. This situation must be distinguished from occult bleeding and from intrathoracic hypertension that may result from a tension pneumothorax [29,30], a massive diaphragmatic hernia [31-34], or intra-abdominal hypertension [36,37]. On rare occasions cardiac tamponade will result from a missed cardiac wound or from liquid accumulation in the pericardial sac after a wound or an incision (Table 2) [100][101][102].…”
Section: The Hypotense or Hypoperfused Trauma Patient In The Icumentioning
confidence: 99%
See 3 more Smart Citations
“…It often results from a mismatch between the fluids required and the fluids administered. This situation must be distinguished from occult bleeding and from intrathoracic hypertension that may result from a tension pneumothorax [29,30], a massive diaphragmatic hernia [31-34], or intra-abdominal hypertension [36,37]. On rare occasions cardiac tamponade will result from a missed cardiac wound or from liquid accumulation in the pericardial sac after a wound or an incision (Table 2) [100][101][102].…”
Section: The Hypotense or Hypoperfused Trauma Patient In The Icumentioning
confidence: 99%
“…The elevated intrathoracic pressure hinders lung expansion and oxygenation. The mechanically ventilated patient shows elevated airway pressures, hypoxemia, and sometimes hypercarbia [31, 36,37]. The physical examination can identify asymmetry in tension pneumothorax and diaphragmatic hernia.…”
Section: The Hypotense or Hypoperfused Trauma Patient In The Icumentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in IAP ≥ 20 mmHg is associated with a marked reduction in cardiac output and oliguria. In a recent study, a mortality rate of up to 64% was reported in patients with urinary bladder pressure over 25 mmHg (grade III) and organ dysfunction, when ACS was due to the presence of intra-abdominal or retroperitoneal pathology (10).…”
Section: Discussionmentioning
confidence: 99%